Lighting up the fire in cold tumors to improve cancer immunotherapy by blocking the activity of the autophagy-related protein PIK3C3/VPS34. Issue 11 (1st November 2020) - Janji, Bassam; Hasmim, Meriem; Parpal, Santiago; De Milito, Angelo; Berchem, Guy; Noman, Muhammad Zaeem
ABSTRACT: Cancer immunotherapy based on Immune checkpoint blockade (ICB) is a promising strategy to treat patients with advanced highly aggressive therapy-resistant tumors. Unfortunately, the clinical reality is that only a small number of patients benefit from the remarkable clinical remissions achieved by ICB. Experimental and clinical evidence claimed that durable clinical benefit observed using ICB depends on the immune status of tumors, notably the presence of cytotoxic effector immune cells. In our paper, we revealed that genetically targeting the autophagy-related protein PIK3C3/VPS34 in melanoma and colorectal tumor cells, or treating tumor-bearing mice with selective inhibitors of the PIK3C3/VPS34 kinase activity, reprograms cold immune desert tumors into hot, inflamed immune infiltrated tumors. Such reprograming results from the establishment of a proinflammatory signature characterized by the release of CCL5 and CXCL10 in the tumor microenvironment, and the subsequent recruitment of natural killer (NK) and CD8 + T cells into the tumor bed. Furthermore, we reported that combining pharmacological inhibitors of PIK3C3/VPS34 improves the therapeutic benefit of anti-PD-1/PD-L1 immunotherapy. Our results provided the proof-of-concept to set-up innovative clinical trials for cold ICB-unresponsive tumors by combining PIK3C3/VPS34 inhibitors with anti-PDCD1/PD-1 and anti-CD274/PD-L1.